2020
DOI: 10.3390/ijerph17113859
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Postural Stability among 13-Year-Old Alpine Skiers

Abstract: This experiment examined changes in body sway after Wingate test (WAnT) in 19 adolescents practicing alpine skiing, subjected to the same type of training load for 4–5 years (10 girls and nine boys). The postural examinations were performed with eyes open (EO), eyes closed (EC), and sway reverenced vision (SRV) in the medial-lateral (ML) and anterior-posterior (AP) planes. The displacement of center of foot pressure (CoP), range of sway (RS), mean sway velocity (MV), way length, and surface area were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Novel research indicates that postural stability in athletes is not influenced by sex [8]. However, some studies noted better postural stability in females, which was suggested to be related to earlier physical and psychological maturation processes [9] and superior sensory integration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Novel research indicates that postural stability in athletes is not influenced by sex [8]. However, some studies noted better postural stability in females, which was suggested to be related to earlier physical and psychological maturation processes [9] and superior sensory integration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic stability testing during a single-leg jump landing did not differentiate between the results of the dominant leg vs. non-dominant leg, but gender differences are found, with women exhibiting higher dynamic postural stability scores in the vertical direction [65]. The postural balance of girls who practice alpine skiing is superior to boys of the same age (13 years) in the mid-lateral plane (ML), and subjecting both genders to the same training can reduce the differences between balance values, but not conditions of muscle fatigue [66]. Fatigue induced by high-intensity exercise applied to Irish university students creates problems of dynamic stability, but women outperform men before and after the exercise, being less affected by fatigue [67].…”
Section: Comparison Of Results With Similar Studies On Balance Values...mentioning
confidence: 99%
“…Moreover, only posture and gate of healthy young men were analyzed. Future studies should investigate the effects of exhaustive exercise on posture in women, to identify gender differences [ 33 ]. A second limitation was the lack of a correlation analysis to show how the levels or the change in the levels of lactate are related to the change in the spatio-temporal gait parameters.…”
Section: Discussionmentioning
confidence: 99%